The Influence of Business Strategy, Service Quality, Governance, Knowledge Management, and Information Technology on Competitive Advantage in Autobus Companies in Java and Surrounding Areas - Hidayah, Nurul; Badawi, Ahmad; Ali, Anees Janee; Prihanto, Hendi (International Journal of Social Science and Business, 2024)
The increasing phenomenon of autobus companies competing with each other has given rise to various strategies to win their competitive advantage, for this reason this research aims to investigate and analyze a number of factors causing competitive ability such as service quality, technology and information systems as well as knowledge management on the competitive advantage of autobus companies. The sample in this study was the manager or management of the AKAP Autobus Company (PO) which manages routes on the islands of Java and Sumatra with samples taken randomly at a number of bus agent locations, terminals and bus company locations, a total of 115 respondents. The data analysis tool uses SEM PLS which is primary data analysis using path analysis to examine latent relationship patterns in the data. The results of the research conclude that the variables business strategy, Governance, Knowledge Management and Information Technology have a significant positive effect on Competitive Advantage. Meanwhile, Service Quality has no effect on Competitive Advantage. The contribution of this research provides an understanding of the management of autobuses so that they can compete in the long term.